Empowering superwomen : Counseling in modern work-family dynamics of Malaysian professionals - Mohd Shahrul, Kamaruddin; Azzahrah, Anuar; Surena, Sabil; Fatahyah, Yahya; Aini Azeqa, Ma’rof; Maizatul Mardiana, Harun (Malque Publishing, 2025)
This study explores the relationship between the need for counselling services, work-family conflict, social support, and mental health among professional women in Malaysia, considering the moderating role for the effects of the need for counselling services on the relationship between work-family conflict and mental health, as well as the relationship between the need for counselling services and social support on mental health. Involving a sample of 362 individuals, this study employs statistical analysis to explore the relationships between the relevant variables. The findings indicate a significant relationship between the need for counselling services and the mental health of professional women in Malaysia (p < 0.05). However, there is no significant relationship between work-family conflict and mental health (p > 0.05). Further analysis also confirms a significant moderating role for the need for counselling services on the relationship between work-family conflict and mental health, as well as for the relationship between the need for counselling services and mental health (p < 0.05). The results of this study contribute significantly to understanding the factors influencing the mental health of professional women in Malaysia. Practical implications include emphasizing the importance of counselling services in supporting their mental well-being, as well as the need for better support strategies in managing work-family conflict. By understanding these factors, supportive measures can be designed to enhance the quality of life for women professionals in this country.